2004
DOI: 10.1212/01.wnl.0000120664.07186.3c
|View full text |Cite
|
Sign up to set email alerts
|

Giant axon and neurofilament accumulation in Charcot–Marie–Tooth disease type 2E

Abstract: The axonal type 2 Charcot-Marie-Tooth disease (CMT2) is phenotypically poorly characterized. Here the authors report a family with a Pro22Ser mutation in the neurofilament-light gene (NF-L; CMT2E) manifesting electrophysiologically as the demyelinating type 1 CMT (CMT1) and pathologically as an axonopathy with giant axons and accumulation of disorganized NF. NF-L should be investigated in CMT2 as well as in CMT1 not associated with the usual genes PMP22, Cx32, and P0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 11 publications
4
81
1
1
Order By: Relevance
“…We believed that this mutation was the underlying cause of the CMT1 phenotype in the FC99 family for the following reasons: cosegregation of the mutation with affected members of the pedigree, no similar mutation in controls (n = 210), well-conserved Pro22 among different species, and the findings of previous reports on the effect of different mutations at the Pro22 site. It seems that codon 22 is one of the mutational hot spots in the NEFL gene because three different Pro22 mutations, including the one found in this study, have been reported (Fabrizi et al 2004;Georgiou et al 2002;Yoshihara et al 2002). Three different families have been reported to have Pro22 mutations: Pro22Ser in a Slovenian family (Georgiou et al 2002) and an Italian family (Fabrizi et al 2004), and Pro22Thr in a Japanese family (Yoshihara et al 2002).…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…We believed that this mutation was the underlying cause of the CMT1 phenotype in the FC99 family for the following reasons: cosegregation of the mutation with affected members of the pedigree, no similar mutation in controls (n = 210), well-conserved Pro22 among different species, and the findings of previous reports on the effect of different mutations at the Pro22 site. It seems that codon 22 is one of the mutational hot spots in the NEFL gene because three different Pro22 mutations, including the one found in this study, have been reported (Fabrizi et al 2004;Georgiou et al 2002;Yoshihara et al 2002). Three different families have been reported to have Pro22 mutations: Pro22Ser in a Slovenian family (Georgiou et al 2002) and an Italian family (Fabrizi et al 2004), and Pro22Thr in a Japanese family (Yoshihara et al 2002).…”
Section: Discussionmentioning
confidence: 48%
“…1b). This mutation was found in the (Yoshihara et al 2002) and c.64C [ T resulting in Pro22Ser (Fabrizi et al 2004;Georgiou et al 2002), but this Pro22Arg mutation was not reported in the inherited peripheral neuropathies mutation database. Amino acids at the mutated site are highly conserved in different species (Fig.…”
Section: Molecular Genetic Analysismentioning
confidence: 96%
See 3 more Smart Citations